Academic Human Resources Development In Realized Excellent and Competitive Higher Education - Fatari; Suseno, Bambang Dwi; Harsasi, Meirani; Pujiwati, Ami (Research Collaboration Community (Rescollacom), 2025)
This study investigates the development of academic human resources (HR) as a critical factor in realizing excellent and competitive higher education institutions. Employing a qualitative descriptive approach, the research was conducted in selected universities in Indonesia that implement strategic HR development. Data were collected via in-depth interviews with university leaders, academic staff, and HR managers, supported by document analysis and observation. The findings highlight four key themes: institutional commitment, strategic academic leadership, digital technology integration, and structural and cultural barriers. Institutional commitment ensures strategic direction, funding, and policies supporting sustainable HR development. Strategic academic leadership fosters an innovative and collaborative academic culture. The integration of digital tools, such as online training and performance management systems, acts as an effective enabler for academic HR development. However, challenges including administrative workload, limited funding, and cultural resistance hinder optimal development. This study contributes a comprehensive understanding of how strategic human resource management and digitalization drive institutional excellence and competitiveness. Policy reforms and continuous leadership support are recommended to overcome existing challenges. The research suggests that universities adopt an integrated approach combining strategic leadership, digital adoption, and cultural transformation to sustainably enhance academic HR and institutional competitiveness in the global era.